2017
DOI: 10.1002/ange.201711031
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and Bis(imidazolidinium ethynyl) Cations and Reduction of the Latter To Give an Extended Bis‐1,4‐([3]Cumulene)‐p‐carboquinoid System

Abstract: Mono-and Bis(imidazolidinium ethynyl) Cations and Reduction of the Latter To Give an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This situation is very similar to the baffling controversy over the magnetic properties of CH because the weak intensity triplet can be masked even with less than 0.1 % impurity of mono radical species, thereby giving a doublet‐like spectrum . Many recently reported close‐shell derivatives, including NHC analogues of TH and CH, also exhibited a similar behavior. Strikingly, a half‐field signal was detected for 7 – 9 at 298 K (Figure and Figures F7–F9 in the Supporting Information) for the forbidden Δ M s =2 transition, which is characteristic for triplets.…”
Section: Figuresupporting
confidence: 53%
“…This situation is very similar to the baffling controversy over the magnetic properties of CH because the weak intensity triplet can be masked even with less than 0.1 % impurity of mono radical species, thereby giving a doublet‐like spectrum . Many recently reported close‐shell derivatives, including NHC analogues of TH and CH, also exhibited a similar behavior. Strikingly, a half‐field signal was detected for 7 – 9 at 298 K (Figure and Figures F7–F9 in the Supporting Information) for the forbidden Δ M s =2 transition, which is characteristic for triplets.…”
Section: Figuresupporting
confidence: 53%
“…Strong σ donors as end‐capping groups of the cumulene chain give their radical species a remarkable stability, with some of these radicals stable even to air . Cumulenes have been known for around 100 years, however, [3]cumulenes that have strong σ donors as terminal groups, such as N‐heterocyclic or cyclic (alkyl)(amino) carbenes (NHCs or CAACs, respectively), have only recently been studied . As discussed above, these types of terminal groups significantly change the properties of the carbon chain with respect to the classical [3]cumulenes and allenes.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these compounds presenta na lmost linear geometry.T here are plenty of [3]cumulenes that have been synthesized, but just as mall fractiono ft hem have been reported with aC -C-C angle of less than 1708,w ith 1658 being the smallest up to now. [24][25][26][27][28][29] This absence of perfect linearity can be attributed to steric repulsions in the crystal, but some theoretical calculationsh ave shown that this slightly bent structure persists or that the bending potential is very shallow in the gas phase. [26,29,30] Thiss hallow potential energy surface could be attributed to other resonant structures,l ike the ones responsible for the bent structures of the heavier E 2 L 2 compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable‐temperature NMR spectroscopy, EPR spectroscopy, and SQUID measurements along with computational studies suggest that diradicaloids 45 have a singlet open‐shell ground state ( 45 a ‐OS), whereas the energy differences with either the singlet closed‐shell ( 45 a ‐CS) or triplet state vary according to the structure of the spacer between the two cAACs. It is notable that closely related compound 46 (with two NHCs instead of cAACs) is EPR silent and has a singlet closed‐shell ground state, as determined by DFT studies …”
Section: Radicals With An Nhc–c Fragmentmentioning
confidence: 96%